Teaching Prepositions in Surah Ar-Rahman: Analysis and Effective Teaching Methods - Muhammad Qadhafi; Aliyatul Jannah; Azmi Ali Muchtar (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This research aims to identify the prepositions in the Arabic grammar and to know the meanings of the prepositions in Surat Al-Rahman. The prepositions, which are simple materials, are not distinguished from the rules of the Arabic language, and has an important role in Arabic grammar, whether in the texts of the Holy Quran or other sciences. Learning prepositions and their rules is important. This research is library research, and it collects all data related to the topic of discussion. After obtaining data and research materials from the library, the researcher collects and classifies all data and materials to suit the research interests. The results of this research are that in Surah Ar-Rahman there are 94 prepositions. Each preposition has many meanings that differ from one another depending on the context of the word. In Surah Ar-Rahman, the preposition